Indocyanine Green (ICG) Fluorescence-Assisted Open Surgery Using the Rubina® Lens System in the Pediatric Population: A Single-Center Prospective Case Series - Ciro Esposito; Claudia Di Mento; Annalisa Chiodi; Mariapina Cerulo; Vincenzo Coppola; Fulvia Del Conte; Francesca Carraturo; Giovanni Esposito; Maria Escolino (Children, 2023)
Introduction: There are scarce papers about the use of fluorescence-guided surgery (FGS) in the open surgical field. This study aimed to assess the usefulness of FGS in an open setting in the pediatric population and to report our preliminary experience using the Rubina® Lens system. Methods: All patients undergoing ICG fluorescence-assisted open surgery over the period September 2022–September 2023 were enrolled. Each surgical procedure was performed using the Rubina® Lens for ICG fluorescence visualization. Results: A total of 25 patients, 14 boys and 11 girls with a median age at surgery of 5.8 years-old (range 0–15), were enrolled. Surgical indications were dermoid/epidermoid cysts of the head (n = 7), lymphangiomas of the head/neck (n = 2), thyroglossal duct cysts (n = 7), gynecomastia (n = 3), preauricular fistula (n = 2), second branchial cleft fistula (n = 1), fibrolipoma of the shoulder (n = 1) and myofibroma of the gluteal/perineal region (n = 2). In all procedures, an intralesional injection of 2.5 mg/mL ICG solution using a 30-gauge needle was administered. No adverse reactions to ICG occurred. Median operative time was 68.6 min (range 35–189). The visualization of ICG-NIRF with the Rubina® Lens was achieved in all cases. No intraoperative complications were reported. Postoperative complications occurred in 3/25 patients (12%), with gynecomastia (n = 1), thyroglossal duct cyst (n = 1) and neck lymphangioma (n = 1), who developed a fluid collection in the surgical site, requiring needle aspiration in outpatient care (Clavien–Dindo 2). Complete mass excision was confirmed with pathology reports. Conclusions: Based on this initial experience, FGS using the Rubina® Lens was very helpful in open surgery, providing enhanced visualization of anatomy and identification of margins, real-time reliability and low complication rate. It was easy to use, time saving, feasible and clinically safe. Previous experience in MIS is necessary to adopt this technology. The accuracy of the injection phase is important to avoid diffusion of the ICG into the perilesional tissue.